HUBUNGAN PENGETAHUAN TENTANG KEMOTERAPI DENGAN KESIAPAN PULANG PASIEN KANKER SERVIKS SETELAH KEMOTERAPI DI RSUP DR. SARDJITO - , RENI KUSUMASTUTI; , Wiwin Lismidiati, S.Kep., Ns., M.Kep., Sp.Kep.Mat. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Patients should know the post- hospitalization management of chemotheraphyâs side effect. Consequently, nurses must provide education related to the management of chemoteraphyâs side effect. Discharge planning education hopefully able to increase patientâs knowledge due to better readiness for hospital discharge. Objective: This study aimed to determine the relationship between knowledge about chemoteraphy and readiness for hospital discharge in patients with cervical cancer after chemotherapy. Research method: This research was an analytical correlational study. This research conducted on 31 respondents of cervical cancer by purposive sampling. Data collection started from August 27th 2012 until January 23th 2013. Data collecting used questionare of knowledge about chemtherapy and Readiness for Hospital Discharge Scale (RHDS) by Weiss& Piacentine (2006). Data analysis used Spearman's rho statistical test. Result: The results of Spearman's rho statistical test showed the value of Ï = 0.371 with a significance p = 0.04. It means, there was a significant positive corelation with frail power corelation between knowledge about chemotherapy with readiness for hospital discharge after chemotherapy . Conclusion: There was relationship between knowledge about chemoteraphy and readiness for hospital discharge in patients with cervical cancer after chemotherapy.